Arkansas Listings in the National Register of Historic Places. - TOMS, J. MASON (Arkansas Historical Quarterly)
The article reports on the listing of the buildings designed by architect Warren D. Segraves to the National Register of Historic Places as of June 2018. Also cited are Segraves' architectural education at University of Arkansas, his parents Samuel P. and Velma D. Segraves, as well as his signature structuralist modern designs.